(untitled) (MAUSAM, 1971)
Study of the amplitudes of the diurnal and semi-diurnal components of the geomagnetic daily variation in H shows that the solar cycle variation in the two components are different and the relative increase from winter to equinox of the amplitude in semi-diurnal component is more than that for the diurnal component.